AB0273 Very high, but not lower, radiographic progression leads to an increase in haq-di. results from the swiss scqm ra cohort. (15th June 2017) - Mueller, R; Thalmann, R; Graf, N; Schulze-Koops, H; Kempis, J von
Abstract : Background: Numerous predictors of radiographic progression in RA patients have been identified over the last years. In general, analyses of radiographic progression in RA rather focus on radiographic non-progression or repair. High radiographic progression in spite of therapy has, to our knowledge not been analysed in detail in the last years, neither in RCTs nor in cohort studies. Objectives: To analyse radiographic, demographical and clinical data in RA patients with high radiographic progression before and after the individual peak radiographic progression. Methods: We included all RA patients from the Swiss registry SCQM with at least two subsequently scored radiographs. Radiographic destruction was scored using the Ratingen erosion score. To analyse high radiographic progression we selected for the highest (peak) radiographic progression in every individual patient for the analysis. The individual peak radiographic progression was analysed in groups as change of Ratingen scores/year: 0-≤10, 10-≤20, 20-≤30, >30 (groups 1–4, follow up 1998 – 2015). The baseline disease characteristics were compared using standard descriptive statistics (Kruskal-Wallis or Chi-square tests). The change of DAS 28 and HAQ-DI scores before and after peak progression was analysed with the Wilcoxon signed rank tests. Results: 3 patients were included into the analysis. 3'049 patients had a peak radiographic progression between 0 and ≤10/year, 773 between 10 and ≤20, 150 between 20 and ≤30, and 61 of >30. All patient groups were within the same age range (mean: 56.5 – 60.5 years). Rheumatoid factor and ACPA were more frequent in patient groups with higher peak radiographic progression (RF: 73.6, 80.0, 88.9, 90.0; ACPA: 66.8, 73.4, 74.3, 82.1, groups 1–4, respectively). When the rate of radiographic progression before and after peak progression was analysed, 69.7%, 74.7%, 76.9%, and 93.3% of the patients had a radiographic progression of 25% or lower as compared to peak progression before and 76.1%, 81.8%, 91.1%, and 93.8% after this peak progression, respectively for patients in groups 1 to 4 (Figure A). The disease activity, as assessed by DAS 28, was significantly higher in all patient groups before peak progression and lower thereafter (Figure B, p<0.001). Average HAQ-DI scores increased after peak radiographic progression in group 4 (Figure C, p=0.005) whereas it is stable or even decreases among the patients of the other patient groups. Conclusions: These data show that higher disease activity precedes radiographic peak progression, which is, if high, overall rare. Radiographic progression before and after the individual peak radiographic progression was far lower as compared to the time of radiographic peak progression. Only the highest individual peak (change of Ratingen score >30/year) radiographic progression was followed by an increase of HAQ-DI scores. Disclosure of Interest: None declared